The impact of macroeconomic variables towards inflation rate in Malaysia / Amira Nurul Afiqah Abdul Rashid and Nursuhadah Ismail - Abdul Rashid, Amira Nurul Afiqah; Ismail, Nursuhadah (Faculty of Business Management, 2016)
The aim of this study is to investigate the impact of macroeconomics variables towards inflation rate in Malaysia. The selected macroeconomic variables or the independent variables used are government spending, money supply and unemployment for period from 1982 to 2014, which the total number of observation is 33, while the dependent variable is inflation rate. The relationship is examined by undertaking regression analysis using time series data that collected from World Bank Database. Both Single Linear Regression and Multiple Linear Regression are used to identify the relationship between dependent and independent variables. From the result, the study shows that government spending and money supply has positive significant relationship towards inflation meanwhile, unemployment has negative insignificant relationship towards inflation. This indicates that government spending and money supply give impacts towards inflation while changes in unemployment does not give impact to inflation rate in Malaysia. The relationship discovered should be useful for public, industries and policy makers as well.